The Correlation between Volatile Compounds Emitted from Sitophilus granarius (L.) and Its Electrophysiological and Behavioral Responses - Lijun Cai; Sarina Macfadyen; Baozhen Hua; Wei Xu; Yonglin Ren (Insects, 2022)
The granary weevil Sitophilus granarius (L.) is one of the most serious primary insect pests of stored products. When S. granarius present in grains, various volatile organic compounds are released as chemical signals which can be used to detect the insects. In this study, volatile chemical compounds released from S. granarius were analyzed using the headspace solid phase micro-extraction (HS-SPME) coupled with gas chromatography (GC)–mass spectrometry (MS) techniques. Two key compounds, 3-hydroxy-2-butanone and 1-pentadecene, were identified from mixed gender of S. granarius adults at high density. Moreover, both male and female adults showed dose-dependent electroantennography (EAG) responses to 3-hydroxy-2-butanone. In behavioral assays, S. granarius was attracted to 3-hydroxy-2-butanone at 0.001 µg/10 µL but repelled at 10 µg/10 µL or higher. S. granarius was consistently repelled by 1-pentadecene at concentrations at 0.001 and 1000 µg/10 µL. 3-hydroxy-2-butanone and 1-pentadecene have considerable potential to offer in the development of new approaches for the monitoring and management of this destructive stored grain insect pest.